A polypropylene composition and its preparation method and application

By adding alpha nucleating agent, hollow glass microbeads and nanomontmorillonite masterbatches to the polypropylene resin composition, the crystallization behavior of the polypropylene resin is solved, and the problem of poor dimensional stability and excessive density of the polypropylene resin during the hot and cold cycle is achieved, and the high dimensional stability and low density of the polypropylene resin are achieved.

CN117004135BActive Publication Date: 2025-03-25KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310932155.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-03-25
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

The existing polypropylene resin compositions have poor dimensional stability and are too high in the hot and cold cycle process, which cannot meet the automotive industry's demand for lightweight and cold and cold cycle resistance.

Method used

Using polypropylene compositions including α nucleating agent, hollow glass microbeads and nanomontmorillonite masterbatches, the crystallization rate is accelerated through α nucleating agent, hollow glass microbeads reduce thermal conductivity and nanomontmorillonite inhibit elastomer convergence, regulate the crystallization behavior of polypropylene resin, and achieve dimensional stability and low density.

Benefits of technology

It significantly improves the dimensional stability of polypropylene resin before and after hot and cold cycles, and reduces the density of the material, meeting the automotive industry's demand for lightweight and hot and cold cycle resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004362001780000021
    Figure BDA0004362001780000021
  • Figure BDA0004362001780000031
    Figure BDA0004362001780000031
  • Figure BDA0004362001780000072
    Figure BDA0004362001780000072
Patent Text Reader

Abstract

The invention discloses a polypropylene composition and a preparation method and application thereof, belonging to the technical field of polymer materials. The polypropylene composition comprises the following components by weight: 100 parts of copolymerized polypropylene resin; 0.05-0.3 parts of α-nucleating agent; 5-30 parts of hollow glass microspheres; 2-10 parts of nano-montmorillonite masterbatch; the true density of the hollow glass is 0.35-0.55 g / cm 3 The nano-montmorillonite masterbatch comprises polyolefin grafted maleic anhydride and nano-montmorillonite; the surface of the nano-montmorillonite is intercalated with dioctadecyl dimethyl quaternary ammonium salt. The present invention reduces the difference in shrinkage before and after the hot and cold cycles of the polypropylene resin and also has a low density through the synergistic effect of the α-nucleating agent, hollow glass microspheres and nano-montmorillonite masterbatch.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically to a polypropylene composition, a preparation method and application thereof. Background Art

[0002] Among automotive parts, polypropylene resin materials are widely used in many systems such as bumpers, dashboards, door panels, etc. Many parts are subject to alternating hot and cold environments during production, testing or use. For example, the temperature of interior environments such as door panels can reach below 0°C in extremely cold conditions, and can reach above 80°C in extremely hot conditions. Therefore, during the loading process, the parts will be subjected to alternating hot and cold cycle tests, and the dimensional changes of the parts involved are usually controlled below 1‰. Therefore, for plastic parts involved in automobiles, especially those with a size of more than 500mm, the dimensional stability of the parts after the alternating hot and cold cycle test is very important.

[0003] During the injection molding process of ordinary copolymerized polypropylene resin, as the injection molding is completed, the polypropylene resin undergoes non-isothermal crystallization at different temperatures and to different degrees from the surface of the workpiece in contact with the low-temperature mold to the core layer away from the mold, causing the material to shrink to a certain extent. This crystallization shrinkage process is uneven and imperfect, which will reduce dimensional stability. Moreover, after experiencing multiple hot and cold cycles, the crystallization behavior of the material changes significantly, and a more uniform and perfect crystallization behavior appears, which will further increase the difference in shrinkage before and after the hot and cold cycles. In addition, the hot and cold cycle process is accompanied by the polymerization of the elastomer in the copolymerized polypropylene resin. The elastomer itself can inhibit the shrinkage of the polypropylene resin. The polymerization of the elastomer will cause some changes in this inhibition behavior, which will further increase the difference in shrinkage before and after the hot and cold cycles. The combined effect of these factors leads to a very large difference in shrinkage before and after the copolymerized polypropylene resin undergoes hot and cold cycles. It can be seen that after the traditional polypropylene resin undergoes hot and cold cycles, the crystallization behavior of the polypropylene resin itself has changed significantly, and the elastomer that inhibits its shrinkage deformation has also changed significantly, resulting in a large difference in shrinkage before and after the hot and cold cycles. Therefore, if the initial dimensions are qualified, the dimensions of the parts will change significantly after the thermal cycle, and the parts will be too large and interfere with the surrounding parts, or too small and there will be obvious gaps between the parts and the surrounding parts. Therefore, it is very important to develop a polypropylene resin composition that is resistant to thermal cycles.

[0004] In addition, with the development trend of the automotive lightweight industry, in addition to the requirement of resistance to cold and heat cycles, polypropylene resin materials also have additional requirements for low density.

[0005] The prior art discloses a polypropylene resin composition with good dimensional stability, comprising a polypropylene resin, an elastomer, an α-nucleating agent, an ultrafine high-silicon talc mineral filler, and an alkali-free borosilicate inorganic glass fiber, which improves the dimensional stability of the polypropylene resin composition under long-term cold and hot cycle conditions. However, its dimensional stability still needs to be further improved. Moreover, a large amount of talc filler is added to the system, which will significantly increase the density of the polypropylene resin, which does not conform to the development trend of the automotive lightweight industry. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing polypropylene resin composition, namely, poor dimensional stability and excessively high density, and to provide a polypropylene composition which can significantly improve dimensional stability and reduce density.

[0007] Another object of the present invention is to provide a method for preparing the polypropylene composition.

[0008] Another object of the present invention is to provide a use of a polypropylene composition in the preparation of automobile bumpers, instrument panels and door panels.

[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0010] A polypropylene composition, comprising the following components in parts by weight:

[0011]

[0012] The true density of the hollow glass is 0.35-0.0.55 g / cm 3 ;

[0013] The nano-montmorillonite masterbatch comprises polyolefin grafted maleic anhydride and nano-montmorillonite;

[0014] The surface of the nano-montmorillonite is intercalated with dioctadecyl dimethyl quaternary ammonium salt.

[0015] The dioctadecyldimethyl quaternary ammonium salt may be dioctadecyldimethylammonium chloride and / or dioctadecyldimethylammonium bromide.

[0016] The test method of the true density of the hollow glass is: using a JL-1206 true density tester to test based on the principle of gas expansion method.

[0017] In the present invention, the α-nucleating agent, hollow glass microspheres, and nano-montmorillonite masterbatch work synergistically to reduce the difference in shrinkage before and after the hot and cold cycles of the polypropylene resin. The inventors speculate that this is because:

[0018] During the molding process of polypropylene resin: α nucleating agent will accelerate the crystallization rate of polypropylene resin, making the initial crystallization more perfect. Hollow glass microspheres can reduce the thermal conductivity of the material, thereby making the heat transfer from the surface layer of the product to the core layer of the product slower, and the product can be more fully crystallized. Nano-montmorillonite is a typical two-dimensional lamellar structure, which can enhance the shear dispersion of copolymerized polypropylene resin elastomers, so that the shrinkage inhibition effect of the elastomer on the polypropylene resin can be fully exerted. When experiencing hot and cold cycles, nano-montmorillonite can inhibit the secondary polymerization of the elastomer due to its lamellar structure, so that the shrinkage inhibition effect of the elastomer on the polypropylene resin does not change much. The present invention utilizes the low thermal conductivity of hollow glass microspheres, the barrier effect of nano-montmorillonite and the accelerated crystallization effect of the nucleating agent to regulate the secondary crystallization behavior of the polypropylene resin, thereby achieving the low-density characteristics of resistance to hot and cold cycles.

[0019] In the present invention, the nano-montmorillonite is modified by intercalation with dioctadecyl dimethyl quaternary ammonium salt and then grafted with polyolefin with maleic anhydride to prepare a master batch in advance. The nano-montmorillonite in the final polypropylene composition product can reach a good dispersion state, and the montmorillonite can reach an intercalation or even exfoliation state and is not easy to agglomerate.

[0020] The polypropylene resin of the present invention is relatively fully crystallized before the cold and hot cycles, and the elastomer is also relatively fully dispersed. Therefore, the crystallization behavior of the polypropylene resin after the cold and hot cycles changes relatively little, and the secondary polymerization of the elastomer caused by the thermal effect is suppressed by the nano-sheet montmorillonite, so that the difference in shrinkage before and after the cold and hot cycles can be small.

[0021] In addition, hollow glass microspheres can reduce the density of the polypropylene composition.

[0022] Preferably, the polypropylene composition comprises the following components in parts by weight:

[0023]

[0024] Preferably, the true density of the hollow glass is 0.45-0.50 g / cm 3 .

[0025] Preferably, the α-nucleating agent is a substituted aryl phosphate nucleating agent and / or a carboxylic acid metal salt.

[0026] Preferably, the polyolefin grafted with maleic anhydride is one or more of polypropylene grafted with maleic anhydride, polyethylene grafted with maleic anhydride or polyolefin elastomer grafted with maleic anhydride.

[0027] More preferably, the polyolefin grafted with maleic anhydride is polypropylene grafted with maleic anhydride (PP-g-MA).

[0028] Preferably, in the nano-montmorillonite masterbatch, the mass ratio of nano-montmorillonite to polyolefin grafted maleic anhydride is (0.4-2.2):1.

[0029] More preferably, in the nano-montmorillonite masterbatch, the mass ratio of nano-montmorillonite to polyolefin grafted maleic anhydride is (0.5-2):1.

[0030] In the present invention, the nano-montmorillonite with dioctadecyl dimethyl quaternary ammonium salt intercalated on the surface can be purchased or made by oneself.

[0031] Preferably, the preparation method of the nano-montmorillonite masterbatch comprises the following steps:

[0032] S1. The montmorillonite is subjected to a thermal reaction with dioctadecyl dimethyl quaternary ammonium salt to obtain a modified nano-montmorillonite, wherein the reaction temperature is 70 to 90°C;

[0033] S2. Mixing the modified nano-montmorillonite in step S1 with polyolefin grafted maleic anhydride, and extruding through an extruder to obtain nano-montmorillonite masterbatch.

[0034] Optionally, the extruder may be a twin-screw extruder, and the extrusion temperature may be 170-190°C.

[0035] Preferably, in the polyolefin grafted with maleic anhydride, the mass grafting rate of maleic anhydride is ≥0.8%.

[0036] More preferably, in the polyolefin grafted with maleic anhydride, the mass grafting rate of maleic anhydride is 0.9 to 1.1%.

[0037] The test method for maleic anhydride grafting rate is acid-base titration. The sample is refluxed with heated xylene for 30 minutes, then refluxed with excess KOH-ethanol standard solution for 1 hour, phenolphthalein is used as an indicator, and excess HCL-isopropanol is used for back titration to the end point to calculate the maleic anhydride grafting rate.

[0038] In practical applications, antioxidants, light stabilizers, lubricants and other additives may also be added according to actual performance requirements.

[0039] The antioxidant may be 0-0.5 parts of a hindered phenol type primary antioxidant, 0-0.5 parts of a phosphite type secondary antioxidant, and 0-0.5 parts of a thioester type secondary antioxidant.

[0040] The light stabilizer may be 0-0.5 parts of a hindered amine light stabilizer.

[0041] The lubricant can be 0-0.5 parts of stearate lubricant.

[0042] The invention also provides a method for preparing a polypropylene composition, which comprises the following steps: mixing copolymerized polypropylene resin, alpha nucleating agent, hollow glass microspheres and nano-montmorillonite masterbatch, and preparing the polypropylene composition through melt blending and extrusion granulation.

[0043] The extrusion temperature is 170-210°C.

[0044] It can be extruded by a single screw extruder.

[0045] The polypropylene composition prepared by the present invention has good dimensional stability, cold and heat cycle resistance and low density, and can be widely used in the preparation of plastic products. The present invention especially protects the application of the polypropylene composition in the preparation of automobile bumpers, dashboards and door panels.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The invention discloses a polypropylene composition, comprising copolymerized polypropylene resin, alpha nucleating agent, hollow glass microspheres and nano-montmorillonite masterbatch. Through the synergistic effect of the alpha nucleating agent, the hollow glass microspheres and the nano-montmorillonite masterbatch, the difference in shrinkage rate before and after hot and cold cycles of the polypropylene resin is small and the polypropylene resin has low density.

[0048] The difference in shrinkage rate of the polypropylene composition of the present invention before and after the hot and cold cycles is less than 0.10%, and can be as low as 0.03%. The density is lower than 0.90g / cm 3 , can be as low as 0.82g / cm 3 . DETAILED DESCRIPTION

[0049] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0050] Copolymer polypropylene resin-1, brand EP548R, copolymer polypropylene resin, provided by CNOOC and Shell Company.

[0051] Copolymer polypropylene resin-2, brand K7100, copolymer polypropylene resin, provided by Yanshan Petrochemical Company.

[0052] α nucleating agent-1, α-type nucleating agent, brand TMP-6, substituted aromatic phosphate salts, provided by Shanxi Chemical Research Institute.

[0053] α nucleating agent-2, α-type nucleating agent, brand HPN-20E, carboxylic acid metal salts, provided by Mericon Corporation.

[0054] Nucleating agent-3, β-type nucleating agent, brand TMB-5, provided by Shanxi Chemical Research Institute.

[0055] Hollow glass microspheres are provided by Zhengzhou Shenglait Hollow Glass Microsphere New Material Co., Ltd., as follows:

[0056] Hollow glass microsphere-1, model HL46, true density 0.46g / cm 3 ;

[0057] Hollow glass microsphere-2, model HL50, true density 0.50g / cm 3 ;

[0058] Hollow glass microsphere-3, model HL55, true density 0.55g / cm 3 ;

[0059] Hollow glass microsphere-4, model HL35, true density 0.35g / cm 3 ;

[0060] Hollow glass microsphere-5, model HL32, true density 0.32g / cm 3 ;

[0061] Hollow glass microsphere-6, model HL60, true density 0.60g / cm 3 .

[0062] Polypropylene grafted maleic anhydride A, PP-g-MA, brand CA100, maleic anhydride grafting rate 1.1%, provided by Arkema.

[0063] Polypropylene grafted with maleic anhydride B, PP-g-MA, brand PC-1, maleic anhydride grafting rate of 0.9%, provided by Nanhai Bochen Company.

[0064] Polyethylene grafted with maleic anhydride, brand name E588, maleic anhydride grafting rate 1.1%, provided by DuPont.

[0065] Polyolefin elastomer grafted with maleic anhydride, brand name N525, maleic anhydride grafting rate 1.1%, provided by DuPont.

[0066] Nano-montmorillonite A, brand number I.44P, nano-montmorillonite A is modified with dioctadecyl dimethyl quaternary ammonium salt, and is provided by Nanocor.

[0067] Nanomontmorillonite B, brand I.30P, nanomontmorillonite is modified with octadecylamine, provided by Nanocor.

[0068] Talc powder, brand TYT-777A, provided by Tianyuan Company.

[0069] In the present invention, the preparation method of nano-montmorillonite masterbatch-1, nano-montmorillonite masterbatch-2, nano-montmorillonite masterbatch-3, nano-montmorillonite masterbatch-4, nano-montmorillonite masterbatch-5, nano-montmorillonite masterbatch-6, nano-montmorillonite masterbatch-7, nano-montmorillonite masterbatch-8, nano-montmorillonite masterbatch-9, and nano-montmorillonite masterbatch-10 is: nano-montmorillonite and polyolefin grafted maleic anhydride are mixed in proportion, and extruded at 170-190° C. by a twin-screw extruder to prepare the nano-montmorillonite masterbatch. Wherein:

[0070] Nano-montmorillonite masterbatch-1 is composed of nano-montmorillonite AI.44P and polypropylene grafted with maleic anhydride A CA100 was prepared at a weight ratio of 1:1.

[0071] Nano-montmorillonite masterbatch-2 is composed of nano-montmorillonite AI.44P and polypropylene grafted with maleic anhydride A CA100 was prepared at a weight ratio of 0.5:1.

[0072] Nano-montmorillonite masterbatch-3 is composed of nano-montmorillonite AI.44P and polypropylene grafted with maleic anhydride A CA100 was prepared at a weight ratio of 2:1.

[0073] Nano-montmorillonite masterbatch-5 is composed of nano-montmorillonite AI.44P and polypropylene grafted with maleic anhydride A CA100 was prepared at a weight ratio of 0.4:1.

[0074] Nano-montmorillonite masterbatch-6 is composed of nano-montmorillonite AI.44P and polypropylene grafted with maleic anhydride A CA100 was prepared at a weight ratio of 2.2:1.

[0075] Nano-montmorillonite masterbatch-7 is prepared from nano-montmorillonite AI.44P and polypropylene grafted maleic anhydride B PC-1 in a weight ratio of 1:1.

[0076] Nano-montmorillonite masterbatch-8 is nano-montmorillonite AI.44P grafted with polyethylene and maleic anhydride E588 was prepared in a weight ratio of 1:1.

[0077] Nano-montmorillonite masterbatch-9 is nano-montmorillonite AI.44P grafted with maleic anhydride on polyolefin elastomer N525 was prepared in a weight ratio of 1:1.

[0078] Nano-montmorillonite masterbatch-10 is nano-montmorillonite B I.30P grafted with maleic anhydride A on polypropylene CA100 was prepared at a weight ratio of 1:1.

[0079] The preparation method of nano-montmorillonite masterbatch-4 is as follows: 2000g of sodium-montmorillonite (provided by Zhejiang Fenghong Company) is dispersed in 180L, 80°C hot water and stirred vigorously; 1350g of dioctadecyl dimethyl ammonium chloride is dissolved in 80°C hot water, and after the sodium-montmorillonite is fully dispersed, the dioctadecyl dimethyl ammonium chloride solution is mixed with the sodium-montmorillonite dispersion, stirred vigorously for 30 minutes, and allowed to stand to obtain a white precipitate. The white precipitate is filtered and washed with water several times until the filtrate cannot cause 0.1mol / L silver nitrate solution to produce precipitation, and then the obtained precipitate is dried, ground and passed through a 200-mesh sieve to obtain a homemade nano-montmorillonite. The homemade nano-montmorillonite is grafted with maleic anhydride A from polypropylene. CA100 was extruded at a weight ratio of 1:1 through a twin-screw extruder at 170-190° C. to obtain nano-montmorillonite masterbatch-4.

[0080] Talc masterbatch: talc and polypropylene grafted with maleic anhydride A CA100 is produced by extruding at 170-190°C through a twin-screw extruder in a weight ratio of 1:1.

[0081] Examples 1 to 18

[0082] A polypropylene composition, comprising the following components in parts by weight:

[0083] Copolymer polypropylene resin; α nucleating agent; hollow glass microspheres and nano-montmorillonite masterbatch,

[0084] The specific content of each component is shown in Table 1 below.

[0085] Table 1 Composition of polypropylene compositions in various embodiments (by weight)

[0086] Project Number 1 2 3 4 5 6 7 8 9 Copolymer polypropylene resin-1 100 100 100 100 100 100 100 100 100 α Nucleating Agent-1 0.15 0.15 0.1 0.2 0.15 0.15 0.15 0.15 α Nucleating Agent-2 0.15 Nucleating agent-3 Hollow glass microsphere-1 15 10 20 15 15 15 15 Hollow glass microsphere-2 15 Hollow glass microspheres-3 15 Hollow glass microsphere-4 Nano-montmorillonite masterbatch-1 5 5 4 8 5 5 Nano-montmorillonite masterbatch-2 5 Nano-montmorillonite masterbatch-3 5 Nano-montmorillonite masterbatch-4 5 Nano-montmorillonite masterbatch-5 Nano-montmorillonite masterbatch-6 Nano-montmorillonite masterbatch-7 Nano-montmorillonite masterbatch-8 Nano-montmorillonite masterbatch-9

[0087] Table 1

[0088]

[0089]

[0090] The preparation method of the above-mentioned polypropylene composition is specifically as follows:

[0091] The components were mixed at 50 rpm for 1 minute, melt-extruded at 170-210° C. through a single-screw extruder, pelletized, and dried to obtain the polypropylene composition.

[0092] Comparative Examples 1 to 16

[0093] A polypropylene composition, comprising the following components in parts by weight:

[0094] Copolymer polypropylene resin; α-nucleating agent; hollow glass microspheres; nano-montmorillonite masterbatch, wherein the specific content of each component is shown in Table 2 below.

[0095] Comparative Example 7 includes the following components: copolymerized polypropylene resin; α-nucleating agent; hollow glass microspheres; nano-montmorillonite A and polypropylene grafted maleic anhydride A.

[0096] Wherein, in comparative example 2, the following components are included: copolymerized polypropylene resin; α-nucleating agent; hollow glass microspheres; and talc masterbatch.

[0097] Table 2 Polypropylene composition composition of each comparative example (by weight)

[0098]

[0099]

[0100] Table 2

[0101] Project Number 9 10 11 12 13 14 15 16 Copolymer polypropylene resin-1 100 100 100 100 100 100 100 100 α Nucleating Agent-1 0.35 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Hollow glass microsphere-1 15 3 35 15 15 15 Hollow glass microsphere-5 15 Hollow glass microsphere-6 15 Nano-montmorillonite masterbatch 1 5 5 5 5 5 1 12 Nano-montmorillonite masterbatch 10 5 Talc Masterbatch

[0102] The preparation method of the above-mentioned polypropylene composition is specifically as follows:

[0103] The components were mixed at 50 rpm for about 1 minute, melt-extruded at 170-210° C. through a single-screw extruder, pelletized, and dried to obtain the polypropylene composition.

[0104] Results

[0105] The polypropylene compositions of the above embodiments and comparative examples were tested by the following performance testing methods:

[0106] Resistance to cold and hot cycles test: According to GBT 15585-1995 standard, the shrinkage rate of the parts obtained by injection molding of the test material for 24 hours is the shrinkage rate before cold and hot cycles. Then the parts are placed in a cold and hot cycle box, and after a cycle of -30℃(4h)~90℃(4h)~-30℃(4h)~90℃(4h)~-30℃(4h)~90℃(4h)~-30℃(4h)~90℃(4h), they are placed for 24 hours according to GBT15585-1995, and the shrinkage rate of the parts measured is the shrinkage rate after cold and hot cycles. The difference in shrinkage before and after cold and hot cycles reflects the material's resistance to cold and hot cycles. The smaller the difference in shrinkage before and after cold and hot cycles, the stronger the material's resistance to cold and hot cycles.

[0107] Density testing is performed according to ISO 1183-2019.

[0108] The specific test results of each embodiment are described in Table 3 below:

[0109] Table 3

[0110]

[0111] Table 3

[0112]

[0113] The specific test results of each comparative example are described in Table 4 below:

[0114] Table 4

[0115]

[0116] Table 4

[0117]

[0118] From the above data, it can be seen that the difference in shrinkage before and after the hot and cold cycles of the polypropylene composition of the present invention is less than 0.10%, and can be as low as 0.03%. In addition, the density of the embodiments is lower than 0.90 g / cm 3 , can be as low as 0.82g / cm 3 , which is lower than the density of ordinary polypropylene resin raw materials 0.90g / cm 3 , the material is very consistent with the lightweight development direction of the automotive industry.

[0119] Comparative Example 1 is direct injection molding of conventional copolymerized polypropylene, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles is too large.

[0120] In Comparative Example 2, the nano-montmorillonite masterbatch was replaced with talcum powder masterbatch, and the difference in shrinkage rate of the parts made of the material before and after the hot and cold cycles was too large.

[0121] Comparative Examples 3-5 lack one of the components of α-nucleating agent, hollow glass microspheres, and nano-montmorillonite masterbatch, so the synergistic effect of the system cannot be exerted, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles is too large.

[0122] The nucleating agent used in Comparative Example 6 is a β-type nucleating agent, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles is also too large. This is because the stability of the β crystal is much lower than that of the α crystal.

[0123] The nano-montmorillonite used in Comparative Example 7 was not pre-prepared into a masterbatch, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles was too large. This is because the montmorillonite is poorly dispersed and easily agglomerated, and cannot fully exert its morphology regulation effect on the elastomer in the polypropylene resin.

[0124] In Comparative Example 8, the amount of α nucleating agent added is too little, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles is too large. This is because the amount of nucleating agent added is too low and the crystallization behavior is not sufficiently promoted.

[0125] In Comparative Example 9, the amount of α nucleating agent added is too much, and the difference in shrinkage rate before and after the hot and cold cycles of the parts made of the material is too large. This is because too high an amount of nucleating agent added will cause local crystallization to be too fast during the injection molding process, resulting in excessive melt strength of the material, causing the hollow glass microspheres to be damaged, resulting in too large a difference in shrinkage rate before and after the hot and cold cycles of the parts made of the material.

[0126] In Comparative Example 10, the amount of hollow glass microspheres added is too little, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles is too large. This is because the hollow glass microspheres have too little inhibitory effect on thermal conductivity.

[0127] In Comparative Example 11, the amount of hollow glass microspheres added was too much, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles was too large. This is because the hollow glass microspheres are easily damaged and have too little inhibitory effect on thermal conductivity efficiency.

[0128] In Comparative Example 12, the true density of the hollow glass microspheres is too small, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles is too large. This is because the true density of the hollow glass microspheres is too small, which will cause their insufficient strength and thus breakage, thereby reducing the inhibitory effect of the hollow glass microspheres on thermal conductivity efficiency.

[0129] In Comparative Example 13, the true density of the hollow glass microspheres is too large, which will also cause a large difference in shrinkage rate before and after hot and cold cycles of the manufactured parts due to insufficient efficiency in suppressing the thermal conductivity.

[0130] In Comparative Example 14, too little nano-montmorillonite masterbatch was added, and the difference in shrinkage rate of the parts made of the material before and after hot and cold cycles was too large. This is because too little nano-montmorillonite masterbatch addition will result in insufficient regulation of the elastomer morphology in the polypropylene resin.

[0131] In Comparative Example 15, the amount of nano-montmorillonite masterbatch added is too much, and the difference in shrinkage rate of the parts made of the material before and after the hot and cold cycles is too large. This is because if the amount of nano-montmorillonite masterbatch added is too much, the nano-montmorillonite will agglomerate, and the elastomer morphology control in the polypropylene resin will be insufficient. At the same time, if the amount of nano-montmorillonite masterbatch added is too large, the hollow glass microspheres will be damaged, and the effect of the hollow glass microspheres will also be negatively affected. Therefore, the difference in shrinkage rate of the parts made of the material before and after the hot and cold cycles is too large.

[0132] In Comparative Example 16, nano-montmorillonite was modified with octadecyl ammonium salt and then prepared into nano-montmorillonite masterbatch. The difference in shrinkage rate of the parts made from the material before and after hot and cold cycles was too large. This may be because the molecular weight of the modifier used to modify the montmorillonite was too small, and the interlayer spacing of the montmorillonite was insufficient, which made it easy for the montmorillonite to agglomerate in the product, and the barrier elastomer aggregation effect of the montmorillonite was difficult to exert.

[0133] It can be seen from Examples 1, 2, 9 and 10 that the true density of the hollow glass microspheres is 0.45-0.50 g / cm 3 , which is more conducive to reducing the difference in shrinkage rate of parts made of materials before and after hot and cold cycles.

[0134] It can be seen from Examples 1, 6-7 and 13-14 that in the nano-montmorillonite masterbatch, the mass ratio of nano-montmorillonite and polypropylene resin grafted maleic anhydride is (0.5-2):1, which is more conducive to reducing the difference in shrinkage rate before and after hot and cold cycles of parts made of the material.

[0135] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A polypropylene composition, characterized in that By weight, it includes the following components: The true density of the hollow glass is 0.35-0.55 g / cm 3 ; The nano-montmorillonite masterbatch comprises polyolefin grafted maleic anhydride and nano-montmorillonite; The surface of the nano-montmorillonite is intercalated with dioctadecyl dimethyl quaternary ammonium salt; The α nucleating agent is a substituted aryl phosphate nucleating agent and / or a carboxylic acid metal salt; In the nano-montmorillonite masterbatch, the mass ratio of nano-montmorillonite to polyolefin grafted maleic anhydride is (0.4-2.2):1; In the polyolefin grafted with maleic anhydride, the mass grafting rate of maleic anhydride is 0.9-1.1%.

2. The polypropylene composition according to claim 1, characterized in that By weight, it includes the following components:

3. The polypropylene composition according to claim 1, characterized in that The true density of the hollow glass microspheres is 0.45-0.50 g / cm 3 .

4. The polypropylene composition according to claim 1, characterized in that The polyolefin grafted with maleic anhydride is one or more of polypropylene grafted with maleic anhydride, polyethylene grafted with maleic anhydride or polyolefin elastomer grafted with maleic anhydride.

5. The polypropylene composition according to claim 1, characterized in that The preparation method of the nano-montmorillonite masterbatch comprises the following steps: S1. The montmorillonite is thermally reacted with dioctadecyl dimethyl quaternary ammonium salt to obtain modified nano-montmorillonite, wherein the reaction temperature is 70 to 90 ° C; S2. Mixing the modified nano-montmorillonite in step S1 with polyolefin grafted maleic anhydride, and extruding through an extruder to obtain nano-montmorillonite masterbatch.

6. The method for preparing the polypropylene composition according to any one of claims 1 to 5, characterized in that: The copolymerized polypropylene resin, alpha nucleating agent, hollow glass microbeads and nano-montmorillonite masterbatch are mixed, melt blended and extruded to prepare the polypropylene composition.

7. Use of the polypropylene composition according to any one of claims 1 to 5 in the preparation of automobile bumpers, instrument panels and door panels.

Citation Information

Patent Citations

  • Low-warp creep-resistant polypropylene composite as well as preparation method and application thereof

    CN102532701A

  • Low-shrinkage modified polypropylene material

    CN105218951A